Absent voices: Help-seeking behaviour among South African male victims of intimate partner violence - Kgatle, Mankwana Othilia; Mafa, Prudence (Technium Social Sciences Journal, 2021)
It remains a huge challenge for most male victims of intimate partner violence to seek help. Abused men seem to lack courage to seek help due to interpersonal and intrapersonal factors that affect their decision to disclose the abuse experienced. This study was aimed at exploring help seeking behaviour of male victims of partner violence in selected rural areas of South Africa. The objectives of the study were to determine men’s views about seeking help and to help improve services for victims of gender-based violence. The study has implemented qualitative approach with exploratory research design. Data was collected through semi structured interviews and was analysed using thematic data analysis. Barriers that prevent men from seeking help include fear of possible ridicule, disbelief, false accusations, and rejection from helping professionals. Feelings of helplessness, perceived lack of confidentiality among professionals and influence of the media hampered help-seeking behaviour of most men in the study. The overall outcome of the study is that most victims appear to lack knowledge of services available for them. It has also been established that male victims are reluctant to seek support from informal networks such as friends, family members, colleagues, and their in-laws. The study recommends that public education, advocacy, and appropriate gender-sensitive intervention programmes be implemented to overcome the effects of violence and to prevent further victimisation.